ROLE AND IMPORTANCE OF NATIONAL GAMES IN KAZAKH SOCIETY IN UPBRINGING OF YOUNG PEOPLE - Kalshabayeva, B.; Imanberlinova, G. (Journal of history, 2018)
In the article the authors pay attention to the role of the traditional culture of the Kazakh people, the role of national games in the Kazakh society, its role in the upbringing of young people. It encourages our young generations for being patriots of their country, to love Motherland, respect for the noble heritage of the people. The authors give description of works by dividing the Kazakh national games into groups. All Kazakh national games, such as «Baige», «Kokpar», «Altyn saka», «Khan talapai», «Kyz-kuu», «Togyzkumalak» and others increases the abilities of children, and attitude to work. Through the game, develops the child`s mind and the concept of heroism. Moreover, it provides such qualities as being loyal, acting fast, strength and patience.